The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/foods12020363
|View full text |Cite
|
Sign up to set email alerts
|

Konjac Glucomannan: An Emerging Specialty Medical Food to Aid in the Treatment of Type 2 Diabetes Mellitus

Abstract: There are many factors causing T2DM; thus, it is difficult to prevent and cure it with conventional treatment. In order to realize the continuous intervention of T2DM, the treatment strategy of combining diet therapy and traditional medication came into being. As a natural product with the concept of being healthy, konjac flour and its derivatives are popular with the public. Its main component, Konjac glucomannan (KGM), can not only be applied as a food additive, which greatly improves the taste and flavor of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 93 publications
0
6
0
Order By: Relevance
“…The presence of insoluble fibre and the formation of a thick gel by glucomannan contributed to the delay in gastric emptying, prolonged satiety, and subsequent reduction in body weight among adults with overweight or obese. 7,8 According to the European Food Safety Authority (EFSA), consuming 3 g of glucomannan in divided doses can effectively reduce body weight in overweight adults. Fasting blood glucose (FBG) levels in rats supplemented with porang glucomannan at a dose of 100 mg/200 g BW exhibited a similar trend to the average body weight and was significantly different compared to the normal group.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of insoluble fibre and the formation of a thick gel by glucomannan contributed to the delay in gastric emptying, prolonged satiety, and subsequent reduction in body weight among adults with overweight or obese. 7,8 According to the European Food Safety Authority (EFSA), consuming 3 g of glucomannan in divided doses can effectively reduce body weight in overweight adults. Fasting blood glucose (FBG) levels in rats supplemented with porang glucomannan at a dose of 100 mg/200 g BW exhibited a similar trend to the average body weight and was significantly different compared to the normal group.…”
Section: Resultsmentioning
confidence: 99%
“…16 These findings align with previous research conducted by Fang, who stated that glucomannan reduces blood glucose levels and lowers the risk of diabetes mellitus type 2. 8 Porang glucomannan also has a prebiotic effect. 17 Another research revealed that supplementation with inulin, another prebiotic substance, improved glucose levels, serum insulin, and HOMA-IR (Homeostatic Model Assessment of Insulin Resistance) in rats model of metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is due to ultrastructural changes resulting in a decreased antioxidant capacity [ 58 , 59 ]. In other words, the levels of enzymatic antioxidants, including superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPX), and thioredoxin (Trx), as well as non-enzymatic antioxidants such as glutathione (GSH), ascorbic acid, and tocopherol, were reduced in response to 131 I [ 60 , 61 ]. Herein, ferroptosis described a novel form of regulatory cell death that was induced by fatal lipid peroxidation [ 62 ], dependent on iron, which was subsequently induced by an oxidation-damaged phospholipid accumulation and associated with the glutathione-dependent antioxidant defense dysfunction mediated by GPX4 via various pathways.…”
Section: Oxidative Stress Dominates 131 I Side Eff...mentioning
confidence: 99%